Green and Efficient Synthesis of Novel Pyrazole based Hydrazineyl-Thiazole Derivatives (International Journal of Scientific Research in Science and Technology, 2025)
A green and efficient protocol for the synthesis of novel pyrazole based hydrazineyl-thiazole derivatives via a two-step procedure is reported. The reaction has been catalyzed by p-TSA using ethanol as green solvent. The present protocol offers several advantages such as broad substrate scope, operational simplicity, high yields and use of environmentally benign solvent.